2009
DOI: 10.1111/j.1600-0501.2009.01748.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a computerized tomography‐guided template‐assisted implant placement system: an in vitro study

Abstract: Computer-assisted implant planning and insertion provides good accuracy. Deviations are mainly related to system and reproducibility errors. Multiple use of drills and titanium sleeves significantly reduces system accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 18 publications
6
47
0
5
Order By: Relevance
“…These results are consistent with the observations of Verhamme and colleagues, who described discrepancies between the guiding elements for the examined NobelGuide TM concept of 0.22 to 0.23 mm . In addition, the present study observed significantly greater deviations for greater implant diameters as attrition of guiding sleeves and drills is a cumulative phenomenon …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the observations of Verhamme and colleagues, who described discrepancies between the guiding elements for the examined NobelGuide TM concept of 0.22 to 0.23 mm . In addition, the present study observed significantly greater deviations for greater implant diameters as attrition of guiding sleeves and drills is a cumulative phenomenon …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, no significant differences between cone beam CT‐ and multislice CT‐based three‐dimensional images or models showing an appropriate accuracy for computer‐aided dentistry were registered by recent studies . Nevertheless, Horwitz and colleagues reported a planning procedure‐related inaccuracy of an average of 0.32 to 0.49 mm . The potential manufacturing error of the stereolithographically manufactured surgical template was calculated to be within a range of 0.1 to 0.2 mm .…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] The surgical templates fabricated by this technology are preprogrammed with individual depth, angulations, mesio-distal, and labio-lingual positioning of the implant. [46,47] 12. A CT scan procedure is performed with a radiographic template fabricated using radio-opaque marker in place.…”
Section: Evolution Of Computer Aided Advanced Radiographic Templatesmentioning
confidence: 99%
“…Die hohe Präzision der verschiedenen Verfahren wurde vielfach bestätigt [11,18,19,20], jedoch weist die Schablonentechnik auch wesentliche Kritikpunkte auf. Übliche additiv vernetzende Kunststoffe sind meist thermolabil, nicht autoklavierbar und damit in der Regel nicht steril einsetzbar.…”
Section: Hintergrund Und Technikunclassified